New serum soluble factors predicting inflammatory and non-inflammatory disability worsening in multiple sclerosis - Rodero-Romero, Alexander; Domínguez-Mozo, María; Monreal, Enric; García-Domínguez, José M.; Villarrubia, Noelia; Fernández-Velasco, José Ignacio; Comabella, Manuel; de la Maza, Susana Sainz; Goicochea Briceño, Haydee; Chico-García, Juan Luís; García-Martínez, María Ángel; Rodriguez-Jorge, Fernando; et al. (Frontiers in Immunology, 2025)
IntroductionSerum neurofilament light chains (sNfL) and glial fibrillary acidic protein (sGFAP) associate respectively with acute inflammation and smoldering disease in relapsing-remitting multiple sclerosis (MS) patients. We explored the proteomic profile associated with the different combinations of low or high levels of sNfL and sGFAP to explore immune mechanisms involved in different MS outcomes.MethodsMulticenter cross-sectional study including 253 treatment-naïve PwMS, and 180 healthy controls (HCs). sNfL and sGFAP levels were measured via SIMOA and patients were classified according to their levels into four groups: NLGL (normal sNfL and sGFAP), NHGL (high sNfL/normal sGFAP), NHGH (high sNfL and sGFAP), and NLGH (normal sNfL/high sGFAP). Serum proteomics were measured using the Olink™ 48 Cytokine panel. Results were analyzed by Kruskal-Wallis tests with Dunn’s post hoc analysis and further corrected by the False Discovery Rate analysis. Q-values below 0.05 were considered as significant.ResultsCompared with HC, patients with low sGFAP concentrations exhibited decreased levels of granulocyte-macrophage colony stimulating factor (GM-CSF), a cytokine inducing innate cell activation q=0.009 for NLGL and q=0.002 for NHGL groups). Conversely, patients with high sGFAP values showed a remarkable decrease of epidermal growth factor (EGF), a cytokine involved in remyelination and axon repair produced by resting astroglia (q<0.0001 for NHGH and NLGH respectively). Additionally, NLGH patients exhibited pronounced decreases in soluble mediators essential for adaptive immune activation, including FLT3LG, TNFSF12, and TNF-α, compared to HC. They also showed broad reductions in chemokines involved in leukocyte recruitment as CCL3, CCL7, and CCL4. The most important decrease was found in CCL2, a chemokine that attracts monocytes and memory T cells to the CNS. NLGH patients showed lower values than HC (q<0.0001), NLGL (q=0.02), NHGL (q=0.02), and NHGH (q=0.03). These findings indicated that NLGH patients experience a reduction of the inflammatory response in the peripheral blood and a decreased immune cell attraction to the central nervous system combined with a lower ability of tissue repair.DiscussionWe identified new molecules implied in the different pathological mechanisms occurring in patients with MS. These biomarkers could improve patient stratification, outcome prediction, and treatment optimization.